Variação espacial e temporal da diversidade e biomassa da comunidade zooplanctônica do reservatório da UHE de Furnas-MG, Brasil - Silva, Lidiane Cristina da (2011)
The UHE Furnas Reservir is located in the state of Minas Gerais and it was built for hydroelectricity generation in 1963, although it is present used for multiple purposes. The zooplankton communities of freshwaters are composed by a variety of species belonging to several taxonomic (Cladocera, Copepoda, Rotifera, Protozoa, larvas de Insecta, Ostracoda, Turbellaria), and are all ecologically important. Many species can be indicators being highly sensitive of environmental conditions The aim of the present work was to analyse the spatial and temporal changes in the species composition, diversity and biomass of zooplankton community as well as their interactions with other environmental variables at the UHE Furnas Reservoir. Samplings were carried out each three months in 36 points in the reservoir, including the two major compartments: Sapucai and Grande dammed portions. Measurements of the main physical and chemical variables were carried out in situ and in the laboratory measurements of nutrients, suspended matter and chlorophyll a concentrations were performed. Zooplankton community was sampled by vertical net hauls with plankton net of 68 μm mesh size. Samples were analyzed regarding the species composition, numerical densities and community biomass. The results obtained indicated the water of the UHE Furnas Reservoir has oligotrophic conditions except in a locality upstream, in River Marimbondo compartment and others located distantly from the dam. The reservoir is thermally and chemically stratified regarding temperature and dissolved oxygen. There are also spatial changes and the reservoir can be divided in three major compartments: Sapucaí River compartment; central portion close to the dam and the northern River Grande compartment. Temporal fluctuations occurred for most variables, with strong differences among the dry and rainy periods. The species richness was high and some species were spatially segregated. Copepoda was the most abundant zooplankton group, both in numbers and biomass. The highest densities and biomass were found in the central portion of the reservoir during the rainy period. In general, the highest concentrations of chlorophyll, zooplankton density and biomass occurred in the Sapucaí River compartment, indicating its higher trophic condition as compared to the more oligotrophic River Grande compartment. Zooplankton biomass as a whole is low compared to other reservoirs, as expected for an oligotrophic system.